Advances in swarm intelligence : 9th International Conference, ICSI 2018, Shanghai, China, June 17-22, 2018, Proceedings. Part II - ICSI (Conference) 2018 : Shanghai, China); Tan, Ying, 1964-; Shi, Yuhui; Tang, Qirong (Cham, Switzerland : Springer, 2018)
The two-volume set of LNCS 10941 and 10942 constitutes the proceedings of the 9th International Conference on Advances in Swarm Intelligence, ICSI 2018, held in Shanghai, China, in June 2018. The total of 113 papers presented in these volumes was carefully reviewed and selected from 197 submissions. The papers were organized in topical sections namely: multi-agent systems; swarm robotics; fuzzy logic approaches; planning and routing problems; recommendation in social media; predication; classification; finding patterns; image enhancement; deep learning; theories and models of swarm intelligence; ant colony optimization; particle swarm optimization; artificial bee colony algorithms; genetic algorithms; differential evolution; fireworks algorithm; bacterial foraging optimization; artificial immune system; hydrologic cycle optimization; other swarm-based optimization algorithms; hybrid optimization algorithms; multi-objective optimization; large-scale global optimization.
Multi-agent systems -- swarm robotics -- fuzzy logic approaches -- planning and routing problems -- recommendation in social media -- predication -- classification -- finding patterns -- image enhancement -- deep learning -- theories and models of swarm intelligence -- ant colony optimization -- particle swarm optimization -- artificial bee colony algorithms -- genetic algorithms -- differential evolution -- fireworks algorithm -- bacterial foraging optimization -- artificial immune system -- hydrologic cycle optimization -- other swarm-based optimization algorithms -- hybrid optimization algorithms -- multi-objective optimization -- large-scale global optimization.
International conference proceedings.
Includes author index.
Online resource; title from PDF title page (SpringerLink, viewed June 20, 2018).
Keywords: Swarm intelligence -- Congresses; Algorithms & data structures; Computers -- Programming -- Algorithms; Swarm intelligence; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.